(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
This study was conducted in the coastal village of Bustan al-Basha (Jabla region) in order to study the reactions of eight Bean inputs as well as a sensitive Control (Gizza 4) and a resistant Control (Ascot) to Ascochyta Blight disease under conditions of artificial infection. The disease severity of the entrance 1 rose from 15.7 (during the paper phase 11-14) To 38.5 and 31.4% during the start-of-contract and fruit phases respectively, the disease severity of the input 5 rose from 15.7% to 38.5 and 40% at the start-of-contract and fruit phases respectively, compared to the sensitive control severity which rose from 28% to 56 and 61.3% during the start-of-contract and fruit phases respectively. The results of the area under the Disease Progression Curve (AUDPC) showed that the rate of progression of the Ascochyta leaf disease in sensitive species Giza 4 was 1.5 times higher than that of both inputs 1 and input 5 . calculating the disease incidence seeds at the end of the season, the lowest incidence rate was found to be 1.35 at input 5 followed by input 1 with an incidence ratio of 4.7 compared with 3.4 at the resistance control and 9.2 at the sensitive control. This allows for the possibility of introducing these inputs into bean cultivation and the possibility of genetic improvement of transplanted inputs and breeds.